2018
DOI: 10.1111/mmi.14138
|View full text |Cite
|
Sign up to set email alerts
|

TgDrpC, an atypical dynamin‐related protein in Toxoplasma gondii, is associated with vesicular transport factors and parasite division

Abstract: Summary Dynamin-related proteins (Drps) are involved in diverse processes such as organelle division and vesicle trafficking. The intracellular parasite Toxoplasma gondii possesses three distinct Drps. TgDrpC, whose function remains unresolved, is unusual in that it lacks a conserved GTPase Effector Domain, which is typically required for function. Here, we show that TgDrpC localizes to cytoplasmic puncta; however, in dividing parasites, TgDrpC redistributes to the growing edge of the daughter cells. By condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 61 publications
7
53
0
Order By: Relevance
“…In contrast, Dnm1 depletion is not lethal in yeast: in absence of fission, the mitochondrial network is only shaped by fusion, and as a result it becomes a long, tubular structure, which can still be transferred to buds during mitosis [17]. Although our analysis suggests that Tg DrpC is essential for mitochondrial fission, which subsequently leads to non-specific secondary defects while the parasite dies, we cannot exclude that TgDrpC has additional functions during parasite replication, as suggested in a recent study [63].…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, Dnm1 depletion is not lethal in yeast: in absence of fission, the mitochondrial network is only shaped by fusion, and as a result it becomes a long, tubular structure, which can still be transferred to buds during mitosis [17]. Although our analysis suggests that Tg DrpC is essential for mitochondrial fission, which subsequently leads to non-specific secondary defects while the parasite dies, we cannot exclude that TgDrpC has additional functions during parasite replication, as suggested in a recent study [63].…”
Section: Discussionmentioning
confidence: 80%
“…No homologs for Mdv1 have been found in Toxoplasma gondii, but there are one Fis1 homolog (TGGT1_263323) and three dynamin-related proteins: DrpA, DrpB, and DrpC. Of these Drp proteins, DrpC, which lacks many of the features required for Drp function, has been associated with mitochondrial division (9). Nonetheless, we and other groups have shown that instead DrpC appears to be involved in vesicle trafficking and endocytosis (9,10).…”
Section: Discussionmentioning
confidence: 81%
“…Of these Drp proteins, DrpC, which lacks many of the features required for Drp function, has been associated with mitochondrial division (9). Nonetheless, we and other groups have shown that instead DrpC appears to be involved in vesicle trafficking and endocytosis (9,10). As Fis1 is the strongest homolog of any putative fission protein in Toxoplasma, we investigated the role of Fis1 in monensin-driven mitochondrial rearrangement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, unlike many higher eukaryotes that possess abundant mitochondria to maintain an overall healthy organelle pool [ 54 ], the fact that these parasites contain a single mitochondrion suggests that they might lack the critical homeostatic mechanisms for mitochondrial maintenance. Such a vulnerability has prompted several groups to undertake research endeavors to identify the proteins and pathways involved in the biogenesis of the mitochondrion [ 55 , 56 , 57 , 58 ]. Likewise, our own upcoming research endeavors are focusing on the identification of the cellular target(s) of the BPZ compounds to illuminate their mechanism of action in the hope of spurring on the development of new treatment regimens against such critical processes.…”
Section: Discussionmentioning
confidence: 99%